Reconstruction of Al-Qur'an-Based Moral Education: A Thematic Study of Maqasid Al-Qur'an in Integrating Moral Knowing, Feeling, and Action Towards Indonesia Emas 2045 - Matsaini Matsaini (Universitas Muhammadiyah Surakarta, 2025)
The phenomenon of moral degradation and disconnection between ethical knowledge and social behavior is a crucial obstacle to Indonesia's vision 2045. This gap often manifests itself in